Influence of Capital Structure, Profitability, and Liquidity on the Value of Tourism Companies Listed on the Indonesia Stock Exchange (BEI) for the 2020–2024 Period. - Wediyanto, Eko; Romadon, Taufik; Putra, Okka Adittio (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
This study aims to analyze the effect of capital structure, profitability, and liquidity on the firm value of tourism sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach was employed using multiple linear regression analysis, based on secondary data from the financial statements of six selected companies. The independent variables in this study include Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE), while firm value is measured using the Price to Book Value (PBV). The results indicate that DER, ROA, and ROE simultaneously have a significant effect on PBV, with a coefficient of determination (R²) of 0.885. Partially, all three variables also show a significant positive effect, with DER having the strongest influence. These findings suggest that capital structure plays a critical role in enhancing firm value in the tourism sector, followed by profitability. The study offers valuable insights for corporate management and investors in formulating optimal financial strategies.